Exploring the Role of Digital Transformation in Sustainability of Islamic Banks: A Systematic Literature Review - Muhammad Ashraf; Muhammad Ejaz; Sadiq Shahid; Ahsan Sheraz Khan (Journal of Accounting and Finance in Emerging Economies, 2025)
Purpose: This study critically interrogates the nexus between digital transformation (DT) and sustainability within Islamic banking, aiming to uncover how emerging technologies catalyze ethical, inclusive, and ESG-aligned financial innovation in developing economies. By contextualizing digital finance within Shariah principles, the review seeks to redefine operational resilience and moral capitalism in the Global South.